Systemic Sequential Therapy of CisGem, Tislelizumab, and Lenvatinib for Advanced Intrahepatic Cholangiocarcinoma Conversion Therapy - Ding, Yuan; Han, Xin; Sun, Zhongquan; Tang, Jinlong; Wu, Yingsheng; Wang, Weilin (Frontiers in Oncology, 2021)
Abstract: intrahepatic cholangiocarcinoma, always diagnosed at an advanced stage in recent years, is of high aggression and poor prognosis. There is no standard treatment beyond first-line chemotherapy and no molecular-targeted agents or immune check-point inhibitors approved for advanced intrahepatic cholangiocarcinoma. Hence, we firstly report an original therapeutic strategy for a 60-year-old patient diagnosed with intrahepatic cholangiocarcinoma categorized as Stage IIIB (T3N1M0) by the American Joint Committee on Cancer staging system. After histopathological examination and next-generation sequencing, the patient was treated with four courses of novel systemic sequential therapy (intravenous gemcitabine 1000 mg/m2 and cisplatin 25 mg/m2 at day 1, day 8; oral Lenvatinib 8 mg per day from day 1 to day 21; intravenous Tislelizumab 200 mg at day 15). Then, the patient achieved partial response and operated right hemihepatectomy, cholecystectomy, and abdominal lymph nodes dissection. Without any perioperative complications, the patient discharged our hospital in perfect condition. Thereafter, the patient continued to use this new regimen one month after surgery for adjuvant therapy and was confirmed without recurrence when we followed up. In a word, we found an effective therapeutic regimen for preoperative advanced intrahepatic cholangiocarcinoma conversion therapy, which may become a new approach in cancer treatment in future.